PERAN INTER PARLIAMENTARY UNION (IPU) TERKAIT ISU PELANGGARAN HAM ETNIS ROHINGYA PADA MASA PEMERINTAHAN SIPIL MYANMAR TAHUN 2011-2016 - Dian Yumansarie; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
IPU is the international organization of parliaments, that makes IPU the only international organization in the world whose members consist of a national parliament from a sovereign country. This makes the role and scope of IPU interesting to see, in this case its about human rights violations during the civilan government in Myanmar. The civilan government made the system of checks and balances to work, where the parliament was active again to conduct surveillance of the government which had never occurred under its military regime. This research gives a new color because so far the resolution of Rohingya-related cases has never been done with a legislative approach.This research aims to explain the extent of the role of IPU in dealing with human rights violation against the Rohingya in Myanmar under the civilian government 2011-2016. The method used in this research is a qualitative method with the type of analytical-descriptive research through literature. The results of this research are that IPU does not have a big role in efforts to protect the human rights violation against the Rohingya in Myanmar because of three main factors, namely: (1) IPU seems to be less aggressive and limiting the scope of its activities, (2) Internal problems possessed by IPU, and (3) Internal barriers resulting from domestic conditions in Myanmar.